PENDEKATAN PSIKOLOGI KOMUNITAS DALAM MEMPREDIKSI PERANAN RASA MEMILIKI KOMUNITAS TERHADAP MUNCULNYA PARTISIPASI MASYARAKAT - Sriwulan Ferindian Falatehan (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2017)
Community in rural areas are subject of development programme, their welfare can be pervaded by building their sense of community and participation in communal setting. This linkage between individuals with their environment can be seen as a social climate which can influence individual behaviour in its social setting from the dimension of relationship orientation. This study focus on the psychological aspects of the community characteristics, which together with the demographic factors could influence community participation within the framework of community development. Thereby the purpose of this study includes: 1) explore the validity of the construct of sense of community; 2) describe the sense of community and its scope; and 3) investigate the influence of the sense of community in eliciting community participation. This sudy is conducted based on quantitative approach implementing survey methods to 200 people in Cikarwang village, Bogor district, West Java province. Data showed that sense of community construct consists of four elements that are: membership, influence, sharing of emotional experience, and fullfillment of needs. (Confirmatory Factor Analysis teqnique at χ2(1)= 0.16, p=0.69; RMSEA=0.00; dan GFI=1.00). The Data also shown that the index of the sense of community is 2.89 which can be categorized as having strong effect on community. There is 65.5% respondents who have this feeling in this category. Their strong feelings to community was shown in each of the 4 elements of sense of community. Sense of community is a factor who can be felt by respondents in the context of RW and RT more than in subvillage; with an F test=3.618 at α=0.002 for RW and F test=4.084 at α=0.000 for RT. Influence of the sense of community to participation can be seen from a model which is identified based on Binomial and Multinomial regression analysis. Binomial regression showed that sense of community and the duration of stay in the village model can predict 74% level of participation. Sense of community with the other demographic characteristics of the community member, such as sex, age, level of education, and working status can elicit participation among members who are male, have at least High School educational background, and still working, (participation ratio as 0.04% compared to those not participated. Multinomial regression showed that sense of community combined with the other demographic factors could predict partcipation in different type of programmes, such as interim government, collective action, or both.